2015
DOI: 10.1108/emjb-09-2014-0030
|View full text |Cite
|
Sign up to set email alerts
|

Britain in bloom? A study into Chinese tourists’ experience

Abstract: Purpose: The purpose of this study is to examine Chinese tourists' experience of Britain based on a conceptual model of tourist satisfaction and destination loyalty, and to identify key issues that tourism organisations could address to provide an excellent experience for Chinese tourists. Practical implications:There are two key challenges for British destination tourism managers: a) to maintain the current quality levels in the attributes that generate tourist satisfaction; and b) to concentrate on improvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…From a learning perspective, evolving retail formats for today's tech-savvy customers that affect shopping behaviour across countries is a call for more academic pursuit to examine attributes that create excellent shopping experiences especially in cross-border destinations (Lin et al, 2015), and additional research on importance ratings of attributes (e.g. Nilsson, 2015b) would help to learn on attributes that are important to consumers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a learning perspective, evolving retail formats for today's tech-savvy customers that affect shopping behaviour across countries is a call for more academic pursuit to examine attributes that create excellent shopping experiences especially in cross-border destinations (Lin et al, 2015), and additional research on importance ratings of attributes (e.g. Nilsson, 2015b) would help to learn on attributes that are important to consumers.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have brought out variations in consumer purchase behaviors in developed vis-a-vis emerging markets (Kumar et al, 2009;Lin et al, 2015;Roberts et al, 2015). Although differences are seen in the consumer needs and solutions in the developed markets, the diversity and fragmentation across emerging markets reveal multi-faceted differences spanning across education, income, religion, literacy, market access, currency, government and regulation, infrastructure, logistics, availability of technology, etc., which have significant management implications owing to variations in customer resources, preferences, and behaviors, across regions (Roberts et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, individual backgrounds and experiences create a unique tourist focus that influences the perceptions of culturally diverse visitors. In a study of Chinese tourists to the UK, Lin et al (2015) found that the Chinese tourists are influenced by culture-specific rather than destination-specific factors. Similar results were obtained by Kapiki et al (2015), who studied Chinese tourists to Greece.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Accessibility or transport infrastructure is one of the crucial destination factors that drive tourist satisfaction and loyalty (Chi & Qu, 2008;Forgas-Coll et al, 2012;Lin, He, & Vlachos Ilias, 2015;Lin, Vlachos, & Ollier, 2018). To access their points of interest within a city destination, tourists may need to navigate through a complex system of different modes of transport, such as metro, light railway, and bus within a city destination (Albalate & Bel, 2010).…”
Section: Introductionmentioning
confidence: 99%